1991
DOI: 10.1002/1097-0142(19911001)68:7<1501::aid-cncr2820680706>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Resectable gastric carcinoma. An evaluation of preoperative and postoperative chemotherapy

Abstract: Patients with locoregional gastric carcinoma often die because of the low rates of curative resection and frequent appearance of distant metastases (mainly peritoneal and hepatic). To evaluate the feasibility of preoperative and postoperative chemotherapy, 25 consecutive previously untreated patients with potentially resectable locoregional gastric carcinoma received two preoperative and three postoperative courses of etoposide, 5‐fluorouracil, and cisplatin (EFP). Ninety‐eight courses (median, five courses; r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(47 citation statements)
references
References 21 publications
4
42
0
1
Order By: Relevance
“…Therefore, prevention of peritoneal carcinomatosis is key to long-term survival. Adjuvant systemic chemotherapy has been recommended as the standard of care for resectable gastric cancer [4,5]; however, peritoneal recurrence is still the most common treatment failure after adjuvant systemic chemotherapy [4][5][6]19]. In this study, peritoneal recurrence also occurred most frequently despite the fact that a number of patients with stages II and III (AJCC/ UICC 6th edition) received adjuvant systemic chemotherapy, except when the patients had poor general condition.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, prevention of peritoneal carcinomatosis is key to long-term survival. Adjuvant systemic chemotherapy has been recommended as the standard of care for resectable gastric cancer [4,5]; however, peritoneal recurrence is still the most common treatment failure after adjuvant systemic chemotherapy [4][5][6]19]. In this study, peritoneal recurrence also occurred most frequently despite the fact that a number of patients with stages II and III (AJCC/ UICC 6th edition) received adjuvant systemic chemotherapy, except when the patients had poor general condition.…”
Section: Discussionmentioning
confidence: 99%
“…Basierend auf diesen überzeugenden Ergebnissen wurde in einer Reihe von Studien daraufhin die neoadjuvante Chemotherapie auch bei Patienten mit potentiell resektablem Magencarcinom evaluiert. Alle publizierten Untersuchungen bei diesem Patientengut (ausschlieûlich unkontrollierte Phase-II-Studien) zeigten übereinstim-mend, daû eine präoperativen Chemotherapie nicht zu einer Erhöhung der postoperativen Letalität oder Morbidität führt [1,2,32]. Die mit der präoperativen Polychemotherapie verbundene Knochenmarksuppression konnte in der Regel durch Dosisreduktion und den Einsatz von knochenmarkstimulierenden Faktoren beherrscht werden.…”
Section: Neoadjuvante Therapie Beim Magencarcinomunclassified
“…Preusser et al [53] demonstrated that an aggressive systemic chemotherapy regimen can have a 50% response rate in advanced gastric cancer, however this less effective in patients with peritoneal metastases. Ajani et al [54] used neoadjuvant chemotherapy and reported the failure of the regimen was most common in patients with peritoneal metastases. Systemic chemotherapy alone for primary gastric cancer with peritoneal metastases is a disappointing plan of management.…”
Section: Neoadjuvant Intraperitoneal and Systemic Chemotherapymentioning
confidence: 74%
“…Therefore, peritoneal implants should be treated via a combined intraperitoneal and intravenous approach. Intravenous chemotherapy has minimal effects on peritoneal metastases and intraperitoneal chemotherapy alone has a less than 30% effect on ascites [34][35][36]53,54] . The bidirectional chemotherapy (intraperitoneal and intravenous) have a response rate of 57% with 100% resolution of ascites.…”
Section: Palliative Benefits To All Patients With Cancerous Ascitesmentioning
confidence: 99%